Joint estimation of crown of thorns (Acanthaster planci) densities on the Great Barrier Reef - MacNeil,M. Aaron; Mellin,Camille; Pratchett,Morgan S.; Hoey,Jessica; Anthony,Kenneth R.N.; Cheal,Alistair J.; Miller,Ian; Sweatman,Hugh; Cowan,Zara L.; Taylor,Sascha; Moon,Steven; Fonnesbeck,Chris J. (PeerJ, 2016)
Crown-of-thorns starfish (CoTS; Acanthaster spp.) are an outbreaking pest among many Indo-Pacific coral reefs that cause substantial ecological and economic damage. Despite ongoing CoTS research, there remain critical gaps in observing CoTS populations and accurately estimating their numbers, greatly limiting understanding of the causes and sources of CoTS outbreaks. Here we address two of these gaps by (1) estimating the detectability of adult CoTS on typical underwater visual count (UVC) surveys using covariates and (2) inter-calibrating multiple data sources to estimate CoTS densities within the Cairns sector of the Great Barrier Reef (GBR). We find that, on average, CoTS detectability is high at 0.82 [0.77, 0.87] (median highest posterior density (HPD) and [95% uncertainty intervals]), with CoTS disc width having the greatest influence on detection. Integrating this information with coincident surveys from alternative sampling programs, we estimate CoTS densities in the Cairns sector of the GBR averaged 44 [41, 48] adults per hectare in 2014.
Keywords: CoTS; Bayesian analysis; Monitoring; Mark-recapture; Data integration